Antioxidant Activity, In Vitro and In Vivo Antidiabetic Efficacy of the Ethanolic Extract from Pyrus communis Leaves. : Antidiabetic Efficacy of the Ethanolic Extract from Pyrus communis L. Leaves - T, Malathi; T, Sivakkumar; T, Sivakkumar (Iranian Journal of Pharmaceutical Sciences, 2025)
One of the more complex long-term metabolic diseases, diabetes is characterised by high blood sugar levels that are either caused by insufficient or inefficient insulin production or use by the body. Antioxidant activity, in vitro and in vivo antidiabetic potency of Pyrus communis leaf ethanolic extract. The study involved collecting Pyrus communis leaves from Tamil Nadu, India, and analyzing their phytochemical properties. In vitro, antioxidant assays were conducted, and total antioxidant activity was determined. In vivo, antidiabetic activity was evaluated in streptozotocin-induced diabetic rats, and the effects of the extract with glibenclamide were evaluated over 4 weeks. Phytochemical screening identified glycosides, phenolics, flavones, flavonoids, terpenoids, and sterols in the extract, highlighting its diverse bioactive components. In vitro, antioxidant activity revealed notable concentration-dependent radical scavenging effects, with DPPH inhibition ranging from 18.86% to 50.97%, ABTS inhibition from 16.01% to 72.42%, and increasing reducing power from 0.2381 to 1.413. The ethanolic extract showed a strong in vitro antidiabetic effect by inhibiting alpha-amylase and alpha-glucosidase in a dose-dependent manner, with inhibition percentages increasing from 13.44% to 64.89% and from 7.84% to 42.79%, respectively. In vivo, studies on STZ-NA-induced diabetic rats revealed protective effects on body weight, with final weights of 163.0±2.08 g and 180.7±3.13 g for lower and higher doses, respectively. Blood glucose levels significantly decreased in test groups, reaching 230.5±2.30 mg/dl and 224.0±3.02 mg/dl, indicating potential antidiabetic efficacy. Histopathological examination revealed preserved pancreatic architecture akin to the normal and standard groups, suggesting protection against diabetes-induced structural alterations. This thorough analysis highlights the antioxidant and antidiabetic properties of P. communis leaf extract, emphasizing its potential as a medicinal agent for treating oxidative stress and diabetes. Further clinical trials and additional mechanistic research are needed to validate this drug's therapeutic efficacy and safety.